Effective Procurement Management and Organisational Performance: Perspectives of the Supply Chain Personnel - CHINOGWENYA, RewardKudzanai; UTETE, Reward (PT Keberlanjutan Strategis Indonesia, 2023)
Although the concept of procurement practices has been studied, the relationship between strategic procurement management and organisational performance has yet to be discovered. Informed by this besetting reality, solid evidence that validates the connection is required to conceptualise procurement management. Thus, the study sought to assess the relationship between procurement management and organisational performance at the leading organisation in the health sector in Zimbabwe. The study adopted a descriptive research design and quantitative research approach. The data was collected from a sample of 40 respondents who comprised the supply chain leaders of a global public health organisation in Zimbabwe. The respondents were randomly selected, and data were collected using a closed-ended questionnaire. The study's key findings indicated that sound procurement management improves organisational performance at a global public health organization in Zimbabwe. The study established that promoting e-procurement system management and strategic buyer-supplier relationships significantly contribute to organisational performance. Therefore, the study recommends that management adopt an electronic procurement system and e-procurement management and forge robust strategic buyer-supplier relationships to improve organisational performance.